Comparison of Short-Chain Fatty Acid (SCFA) and Interleukin-10 (IL-10) Levels in Patients with Systemic Lupus Erythematosus (SLE) Compared to Healthy Populations at RSUP Dr. Mohammad Hoesin Palembang - Nova Kurniati; Eddy Mart Salim; Yuniza; Tiara Rasmita; Amelia Farianty (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. Systemic lupus erythematosus (SLE) is a prototypical autoimmune disease with various significant diseases, where SLE can affect the entire population in the world. This study aims to compare and analyze differences in the composition of the gut microbiota of SLE patients compared to healthy controls based on SCFA examination in Indonesia. Methods. The type of research conducted in this research is an analytical observational study with a case-control design. The research was conducted at Dr. RSUP. Mohammad Hoesin Palembang from October 2020 to October 2021. The sample in this study was divided into two groups, namely, the case group, and the control group. The case group was all SLE patients who met the inclusion criteria, while the control group was a healthy population who did a medical check-up at Dr. RSUP. Mohammad Hoesin Palembang. SCFA examination was carried out using Gas Chromatography-Mass Spectrometry (GCMS) from fecal samples. Results. The results showed that there were two groups of SCFA values, namely the normal group and the microbiota dysbiosis group where the SCFA value was low or less than 4. in the SLE and normal populations where there were 6 SLE subjects who had normal SCFA values or 37.5% and there were 10 SLE subjects who experienced microbiota dysbiosis. or 62.5%. In the healthy population group, all subjects had SCFA values that were included in the normal category, namely 16 subjects or 100%. Based on the severity of SLE using the SLEDAI MEX score, all SLE patients in the study were in the active or category flare where the SLEDAI MEX score was > 5. Conclusion. Patients with microbiota dysbiosis tended to have an LES of 7,222 or 7 times greater than patients who did not have microbiota dysbiosis or had normal SCFA values.